Unitarization of representations of a partially ordered set associated with a graph $\tilde{E}_6$ - Yakymenko, D. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
It is shown that any Schur representation of a poset associated with a graph $\tilde{E}_6$ can be unitarized with a certain character. The description of characters for which it is possible to unitarize the Schur representations of $\tilde{E}_6$ is presented.